El Excentrico, 1973-02-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 20, 1873 [20 de febrero de 1973]. No volume or issue number. Cover has a photograph of Rebecca Rios, a dancer with the Rudy Baca Orchestra.